Respuestas
Respuesta dada por:
15
^-^
Para calcular "a" haremos lo siguiente
![(2 + 1)(2 + 1)(a + 1) = 45 \\ \\ 3 \times 3 \times (a + 1) = 45 \\ \\ 9(a + 1) = 45 \\ \\ a + 1 = 5 \\ \\ a = 4 (2 + 1)(2 + 1)(a + 1) = 45 \\ \\ 3 \times 3 \times (a + 1) = 45 \\ \\ 9(a + 1) = 45 \\ \\ a + 1 = 5 \\ \\ a = 4](https://tex.z-dn.net/?f=%282+%2B+1%29%282+%2B+1%29%28a+%2B+1%29+%3D+45+%5C%5C++%5C%5C+3+%5Ctimes+3+%5Ctimes+%28a+%2B+1%29+%3D+45+%5C%5C++%5C%5C+9%28a+%2B+1%29+%3D+45+%5C%5C++%5C%5C+a+%2B+1+%3D+5+%5C%5C++%5C%5C+a+%3D+4)
Para calcular "a" haremos lo siguiente
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años